Cholesterol expels ibuprofen from the hydrophobic membrane core and stabilizes lamellar phases in lipid membranes containing ibuprofen. Issue 24 (28th June 2015) - Alsop, Richard J.; Armstrong, Clare L.; Maqbool, Amna; Toppozini, Laura; Dies, Hannah; Rheinstädter, Maikel C.
<x xml:space="preserve">Abstract</x> The presence of cholesterol in lipid membranes with ibuprofen suppresses partitioning of ibuprofen in the lipid tail groups and stabilizes lamellar membrane phases.